Combined physical and psychological programmes plus alternative therapies for back pain - Hlavsova MSc, MCSP, HPC, Anna (Henry Stewart Talks, 2015)
Increasing prevalence of back pain and its impacts, The biopsychosocial model, Combined physical and psychological programs, Alternatives: online pain management program, complementary and alternative medicine